URBAN FIRE DISASTER MITIGATION POLICY (Case Study of Fires in the City of Jakarta) - Taufiqurokhman , Taufiqurokhman; Satispi, Evi; Trustisari, Hastin; Supangkat, Gatot (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
The Jakarta City (DKJ) area which is prone to fire is in the high category, where the biggest factor causing electrical short circuits is 90 percent. The research objective is to describe the fire disaster mitigation efforts carried out by the DKJ Fire and Rescue Service (Gulkarmat). The research uses qualitative descriptive methods. Key informant, Head of the DKJ Gulkarmat Service. Currently, a snowball search is being carried out for informants, namely the Head of the Fire Prevention Division of Gulkarmat DKJ. Data collection techniques include interviews, observations, and documentation studies with interactive model data analysis techniques. The research results show that fire disaster mitigation efforts carried out by the DKJ Fire and Rescue Service (Gulkarmat) have been carried out well, but need to be improved. Education and outreach is needed to the DKJ community regarding fire mitigation, with a massive outreach design and required education, outreach, supervision and evaluation.